Cyber intelligence-driven risk : how to build and use cyber intelligence for business risk decisions - Moore, Richard O., III, 1971- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2021)
"The objective of the book will be approached from building a functional cyber intelligence driven risk program and explaining in granular detail how each function and capability can be properly leveraged to make informed business decisions in the era of increased emergent cyber threats and attacks. Readers will be able to: Build, buy, or outsource a functioning cyber intelligence driven risk program Understand the functional capabilities needed to have an effective program Know how to turn cyber intelligence into business decisions Effectively use cyber intelligence to support Enterprise Risk Management programs Reduce the impact of cyber events through intelligence for many business operations leveraging new technologies. Discern how can an effective cyber intelligence driven risk program influence mergers and acquisitions and the benefits of predictive cyber intelligence analytics. Reduce loss from cyber events for the organization"--
Objectives of a cyber intelligence-driven risk program -- Importance of cyber intelligence for businesses -- Military to commercial viability of the CI-DR program -- CI-DR security program components -- Functional capabilities of the CI-DR program -- CI-DR key capability next-generation security operations center -- CI-DR key capability cyber threat intelligence -- CI-DR key capability forensic teams / Dr. Steven Johnson -- CI-DR key capability vulnerability management teams / Derek Olson -- CI-DR key capability incident response teams / Dr. Steven Johnson -- DI-DR collection components -- CI-DR stakeholders / Steve Dufour.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 15, 2020).
John Wiley and Sons
Keywords: Business enterprises -- Security measures; Data protection; Cyber intelligence (Computer security); Risk management; Risk Management; Entreprises -- x; Protection de l'information (Informatique); Surveillance des menaces informatiques; Gestion du risque; risk management; Business enterprises -- Security measures; Cyber intelligence (Computer security); Data protection; Risk management